glocalization Glocalization and TESOL in Thailand (Pascasarjana Universitas HKBP Nommensen, 2020)
This paper investigates the roles and status of English as an international language, and the use of English as the ASEAN lingua franca. The roles of English have been changed due to globalization. When English is used as a global language, non-native speakers of English around the world, who have different cultural background and different first language increasingly use and localize English for communicating and expressing their ideas, concepts and cultures. This leads to the concept of “glocalization”. The term “glocalization” and its interpretation are addressed and clarified. Additionally, the paper reflects the challenges in teaching and learning English as lingua franca (ELF) in Thailand, before moving to the implication of “glocalization” in English teaching and learning.